Genu Recurvatum versus Fixed Flexion after Total Knee Arthroplasty - Koo, Kevin (Clin Orthop Surg, 2016)
BACKGROUND: To date, there is no study comparing outcomes between post-total knee replacement genu recurvatum and fixed flexion. This study aims to provide data that will help in deciding which side to err on when neutral extension is not achieved. METHODS: A prospective cohort study of primary total knee arthroplasties was performed, which compared the 6-month and 2-year clinical outcomes between fixed flexion and genu recurvatum deformities at 6 months. RESULTS: At 6 months, knees in genu recurvatum did better than knees in fixed flexion deformity in terms of knee flexion. However, at 2 years, knees in fixed flexion deformity did better in terms of knee scores and showed better improvement in the degree of deformity. CONCLUSIONS: We conclude that it is better to err on the side of fixed flexion deformity if neutral alignment cannot be achieved.